2021
DOI: 10.3390/s22010291
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection in Asset Degradation Process Using Variational Autoencoder and Explanations

Abstract: Development of predictive maintenance (PdM) solutions is one of the key aspects of Industry 4.0. In recent years, more attention has been paid to data-driven techniques, which use machine learning to monitor the health of an industrial asset. The major issue in the implementation of PdM models is a lack of good quality labelled data. In the paper we present how unsupervised learning using a variational autoencoder may be used to monitor the wear of rolls in a hot strip mill, a part of a steel-making site. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Prognostics predict future system performance, while diagnostics identify current issues through performance analysis. Among the reviewed literature, eleven studies focused on prognostics (Garouani et al, 2022;Gashi et al, 2023;Ghasemkhani et al, 2023;Hajgató et al, 2022;Hermansa et al, 2021;Jakubowski et al, 2021;Kononov et al, 2023;Kuzlu et al, 2020;Serradilla et al, 2021;Upasane et al, 2021;Wu et al, 2021), three on anomaly detection (Choi et al, 2022;Langone et al, 2020;Mey & Neufeld, 2022), and two on both prognostics and diagnostics (Serradilla et al, 2021;Steurtewagen & Van den Poel, 2021). Notably, none focused solely on diagnostics, revealing a significant research gap.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Prognostics predict future system performance, while diagnostics identify current issues through performance analysis. Among the reviewed literature, eleven studies focused on prognostics (Garouani et al, 2022;Gashi et al, 2023;Ghasemkhani et al, 2023;Hajgató et al, 2022;Hermansa et al, 2021;Jakubowski et al, 2021;Kononov et al, 2023;Kuzlu et al, 2020;Serradilla et al, 2021;Upasane et al, 2021;Wu et al, 2021), three on anomaly detection (Choi et al, 2022;Langone et al, 2020;Mey & Neufeld, 2022), and two on both prognostics and diagnostics (Serradilla et al, 2021;Steurtewagen & Van den Poel, 2021). Notably, none focused solely on diagnostics, revealing a significant research gap.…”
Section: 1mentioning
confidence: 99%
“…Ensemble Learning (EL) offered diverse algorithmic solutions and found utility in the prognostics realm of manufacturing industries (Garouani et al, 2022). Despite their complexity, other methods like Balanced K-Star, Multi-Layer Perceptron (MLP), Extreme Learning Machine (ELM), and Transfer Learning (TL) provide alternative approaches, as do Deep Convolutional AutoEncoders (Hajgató et al, 2022;Huang et al, 2006;Jakubowski et al, 2021;Serradilla et al, 2021). Diagnostics in PdM have been less explored, with only a few studies touching on it (Serradilla et al, 2021).…”
Section: 2mentioning
confidence: 99%
“…For example, autoencoders have been successfully used for feature extraction [ 5 ], multi-sensory data fusion [ 6 ], fault diagnosis [ 7 , 8 ], and anomaly detection [ 9 ] because they do not require prior knowledge of the data and can compress and fuse multi-sensory data. Autoencoders are not as efficient at reconstruction compared to generative adversarial networks (GANs) [ 10 ], which allows GANs to solve the class imbalance problem [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpretability of neural network models is still considered only in very few publications that include a mention of PdM [ 34 ]. Even among them, the issue has been raised only for models of RUL prediction [ 35 , 36 ] and anomaly detection [ 9 ]. It was also observed that the analysis of the contribution of features was often limited to the calculation of SHAP values only, without any hypotheses being put forward and confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of autoencoder methods, derivative methods such as the denoising autoencoder [ 25 ], sparse autoencoder [ 26 ], and stacked autoencoder [ 27 ] have been invented. In the field of PHM research, the autoencoder has also been gradually applied to anomaly detection [ 28 , 29 ], RUL prediction [ 30 ], fault diagnosis [ 31 , 32 ], and health status assessment [ 33 ].…”
Section: Introductionmentioning
confidence: 99%